2013
DOI: 10.1037/a0033770
|View full text |Cite
|
Sign up to set email alerts
|

Music through the ages: Trends in musical engagement and preferences from adolescence through middle adulthood.

Abstract: Are there developmental trends in how individuals experience and engage with music? Data from 2 large cross-sectional studies involving more than a quarter of a million individuals were used to investigate age differences in musical attitudes and preferences from adolescence through middle age. Study 1 investigated age trends in musical engagement. Results indicated that (a) the degree of importance attributed to music declines with age but that adults still consider music important, (b) young people listen to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
292
5
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(329 citation statements)
references
References 60 publications
27
292
5
5
Order By: Relevance
“…Studies have reported that females are more likely to prefer Chart Pop and Pop, whereas males are more likely to prefer Blues and Jazz (Bonneville-Roussy et al, 2013;Colley, 2008); however, no gender differences were observed in the preference of these genres in our study.…”
Section: Gender Differences In Musical Preferencescontrasting
confidence: 97%
See 2 more Smart Citations
“…Studies have reported that females are more likely to prefer Chart Pop and Pop, whereas males are more likely to prefer Blues and Jazz (Bonneville-Roussy et al, 2013;Colley, 2008); however, no gender differences were observed in the preference of these genres in our study.…”
Section: Gender Differences In Musical Preferencescontrasting
confidence: 97%
“…The STOMP-R is a 21-item self-report measure assessing the liking for 21 musical genres by using a seven-point rating scale (1 = dislike, 7 = like; Bonneville- Roussy et al, 2013). Although the original STOMP-R comprises 23 items or genres, two of them (soundtracks and oldies) were removed in this study because the interpretation might be influenced by age (Bonneville-Roussy et al, 2013).…”
Section: Stomp-rmentioning
confidence: 99%
See 1 more Smart Citation
“…Early personality psychologists such as Cattell and colleagues argued that musical preferences are manifestations of non-conscious aspects of personality, which provide a window into understanding the unconscious mind (Cattell & Anderson, 1953;Cattell & Saunders, 1954). However today, researchers (Rentfrow, Goldberg, & Levitin, 2011;Bonneville-Roussy, Rentfrow, Xu, & Potter, 2013) have adopted an approach aligned with interactionist theories (Buss, 1987;Swann, Rentfrow, & Guinn, 2002), positing that people seek out music and musical environments that reflect and reinforce more explicit and observable characteristics and traits. The correlations between musical preferences and psychological constructs such as personality traits (Rentfrow & Gosling, 2003), values (Boer et al, 2011) and age demographics (Bonneville-Roussy et al, 2013) have been studied, and convergence across many studies from varied geographical regions (Rentfrow & Gosling, 2003;George, Stickle, Rachid, & Wopnford, 2007;Delsing, ter Bogt, Engels, & Meeus, 2008;Zweigenhaft, 2008;Brown, 2012;Dunn, de Ruyter, & Bouwhuis, 2012;Langmeyer, Guglhör, & Tarnai, 2012) has provided clear evidence that these constructs are linked in a similar fashion.…”
Section: Musical Preferencesmentioning
confidence: 99%
“…Early personality psychologists such as Cattell and colleagues argued that musical preferences are manifestations of non-conscious aspects of personality, which provide a window into understanding the unconscious mind (Cattell & Anderson, 1953;Cattell & Saunders, 1954). However today, researchers (Rentfrow, Goldberg, & Levitin, 2011;Bonneville-Roussy, Rentfrow, Xu, & Potter, 2013) have adopted an approach aligned with interactionist theories (Buss, 1987;Swann, Rentfrow, & Guinn, 2002), positing that people seek out music and musical environments that reflect and reinforce more explicit and observable Empirical Musicology Review Vol. 10, No.…”
mentioning
confidence: 99%